The Use of Calixarenes in Asymmetric Catalysis - Li, Zheng-Yi; Chen, Jia-Wen; Liu, Ying; Xia, Wei; Wang, Leyong (Current Organic Chemistry, 2011)
The use of calixarenes in asymmetric catalysis was described. The current progress of asymmetric catalysts based on calixarene scaffold for the enantioselective reactions including allylation, alkylation, addition of diethylzinc to benzaldehyde, Micheal-type addition, aldol reaction, hydrogenation, Friedal Crafts reaction, epoxidation, hydroformylation, and Biginelli reaction was illustrated. In these cases, calixarenes were used as organocatalysts or ligands in metal-catalyzed asymmetric reactions.
Keywords: organocatalyst